2008
DOI: 10.1080/14622200802279898
|View full text |Cite
|
Sign up to set email alerts
|

Residual tobacco smoke pollution in used cars for sale: Air, dust, and surfaces

Abstract: Regular tobacco use in the enclosed environment of a car raises concerns about longer-term contamination of a car's microenvironment with residual secondhand smoke pollutants. This study (a) developed and compared methods to measure residual contamination of cars with secondhand smoke, (b) examined whether cars of smokers and nonsmokers were contaminated by secondhand smoke, and (c) how smoking behavior and restrictions affected contamination levels. Surface wipe, dust, and air samples were collected in used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 14 publications
3
70
0
4
Order By: Relevance
“…Our research has found that indoor surfaces, dust, and air in smokers ' homes showed nicotine concentrations 5 -7 times higher than nonsmokers ' homes, and homes of smokers who reported always smoking outside had intermediate levels of contamination ( Matt et al, 2004 ). Cars of smokers without car smoking bans showed signifi cantly higher levels of nicotine in dust, on surfaces, and in the air compared with nonsmokers ' cars with smoking bans ( p < .001), and dust and surface nicotine in cars of smokers who had imposed car smoking bans were at similar levels as for smokers ' cars without bans ( Matt et al, 2008 ). Young children are at high risk of SHSe through dust and surface contamination because they spend more time near fl oors.…”
Section: Nicotine Contamination and Thirdhand Exposurementioning
confidence: 81%
“…Our research has found that indoor surfaces, dust, and air in smokers ' homes showed nicotine concentrations 5 -7 times higher than nonsmokers ' homes, and homes of smokers who reported always smoking outside had intermediate levels of contamination ( Matt et al, 2004 ). Cars of smokers without car smoking bans showed signifi cantly higher levels of nicotine in dust, on surfaces, and in the air compared with nonsmokers ' cars with smoking bans ( p < .001), and dust and surface nicotine in cars of smokers who had imposed car smoking bans were at similar levels as for smokers ' cars without bans ( Matt et al, 2008 ). Young children are at high risk of SHSe through dust and surface contamination because they spend more time near fl oors.…”
Section: Nicotine Contamination and Thirdhand Exposurementioning
confidence: 81%
“…12 En 2008 se reportaron hallazgos similares en los autos. 13 Se detectaron cantidades significativamente mayores en el polvo (media de 19.51 μg/g) y en los tableros (media de 8.61 μg/ m 2 ) de 78 vehículos pertenecientes a personas que fumaban en sus vehículos que en el polvo (media de 3.37 μg/g) y en los tableros (media de 0.06 μg/m 2 ) de 20 vehículos de no fumadores. Ocho fumadores habían impuesto una prohibición de fumar en sus vehículos durante por lo menos 12 meses.…”
Section: Breve Historia Del Htmunclassified
“…Such contamination can be a source of thirdhand exposure when the child comes in contact with contaminated surfaces or breathes the air when such contamination " off-gasses " ( Matt et al, , 2008a. Children are more likely to engage in fl oor contact and hand-to-mouth behavior (e.g., putting contaminated objects in their mouths), and, compared with adults, their higher rate of respiration may result in greater inhalation of off-gassing from cigarette smoke contaminants.…”
Section: Addressing " Thirdhand " Exposurementioning
confidence: 99%
“…Parents are sensitive when studies use cotinine biomarkers, nicotine wipes, air dosimeters, and vacuuming of dust samples from homes and cars ( Matt et al, , 2008a.…”
Section: Engineering Social Contingenciesmentioning
confidence: 99%